Geochemical evolution of Late Eocene-Oligocene magmatism on the Shmidt Peninsula (Northern Sakhalin). - Rasskazov, S V; Simanenko, V P; Malinovsky, A I; Yasnygina, T A (PANGAEA, 2007)
Middle Cenozoic evolution of magmatism in the Schmidt Peninsula between 37 and 25 Ma began with eruptions of subalkaline and moderately alkaline andesite, latite, trachyandesite, and trachyrhyolite lavas and ended with subvolcanic intrusions of highly alkaline strongly undersaturated essexites. According to trace element data magmatism evolved from melting of a mantle source in the zone of ocean-continent plate convergence to small degree partial melting in the lithospheric mantle at the final stage. This succession is generally typical for Late Cenozoic continental-margin magmatism in the Southeast Russia. Similarity in the Middle and Late Cenozoic stages of magmatism is an evidence for their individual significance.
(Table 1) Chemical composition of Middle Cenozoic magmatic rocks from the Schmidt Peninsula, North Sakhalin
Keywords: Aluminium oxide; Archive of Ocean Data; ARCOD; Barium; Beryllium; Caesium; Calcium oxide; Cerium; Chromium; Cobalt; Copper; Dysprosium; Erbium; Europium; Gadolinium; Gallium; Hafnium; Holmium; ICP-MS, Inductively coupled plasma - mass spectrometry; Iron oxide, Fe2O3; Iron oxide, FeO; Lanthanum; Lead; Lithium; Lutetium; Magnesium oxide; Manganese oxide; Molybdenum; Neodymium; Nickel; Niobium; Phosphorus oxide; Potassium oxide; Praseodymium; Rock type; Rubidium; Sakhalin Island; Samarium; Scandium; Schm-03/1; Schm-03/10; Schm-03/11; Schm-03/12; Schm-03/2; Schm-03/3; Schm-03/39; Schm-03/4; Schm-03/40; Schm-03/5; Schm-03/6; Schm-03/7; Schm-03/7-1; Schm-03/8; Schm-03/9; Silicon dioxide; Sodium oxide; Strontium; Sum; Tantalum; Terbium; Thorium; Thulium; Tin; Titanium dioxide; Tungsten; Uranium; Vanadium; Water in rock; Wet chemistry; Ytterbium; Yttrium; Zinc; Zirconium